1982
DOI: 10.1103/physrevlett.48.742
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Macroscopic Stability Limits in a Tandem Mirror

Abstract: A limit to the ratio of central-cell to plug p of 1.8 ± 1.0 is measured in the Phaedrus tandem mirror for central-cell jS's of 2% to 5%. This is consistent with the limiting ratio of 2.0 predicted for interchange stability, and is the first experimental test of the effect on the interchange limit from varying the plasma pressure along a magnetic field line in a tandem-mirror configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Here the quantity Γ ks is related to the particle flux per unit magnetic flux Γ ks from a single end of the tandem mirror as indicated in (4). The spread in magnetic moments of the kinetic stabilizer beam is determined by ∆µ; we use µ T = E 0 /B T where the subscript T refers to the target position; the values of ∆µ and µ T effects the maximum density at the target.…”
Section: Kstm Model a Distribution Of Ions In The Kinetic Stabilmentioning
confidence: 99%
“…Here the quantity Γ ks is related to the particle flux per unit magnetic flux Γ ks from a single end of the tandem mirror as indicated in (4). The spread in magnetic moments of the kinetic stabilizer beam is determined by ∆µ; we use µ T = E 0 /B T where the subscript T refers to the target position; the values of ∆µ and µ T effects the maximum density at the target.…”
Section: Kstm Model a Distribution Of Ions In The Kinetic Stabilmentioning
confidence: 99%
“…More detailed results on MHD stability experiments in Phaedrus are described elsewhere. 13 We have shown that a tandem-mirror plasma with isolated end plugs can be sustained by rf and gas fueling for 8 ms beyond gun turnoff. This time appears to be limited only by the rf pulse length and is much longer than the characteristic decay times of the plugs and central cell.…”
mentioning
confidence: 99%
“…1 " 3 Weighting of the good field-line curvature in anchor ceils with sufficient plasma pressure provides interchange stability. 4 Disadvantages of this design are the enhanced radial ion loss due to the nonaxisymmetric field regions associated with the minimum-\B\ ceils 5 and the difficulty and expense in construction of the necessary coil sets. At present there is a significant effort directed toward the design of inter change-stable axisymmetric tandem mirrors.…”
mentioning
confidence: 99%